Wide-Field (15 × 9 mm) Swept-Source Optical Coherence Tomography Angiography Following Plaque Radiotherapy of Choroidal Melanoma: An Analysis of 105 eyes. Issue 4 (July 2020) - Lim, Li-Anne S.; Camp, David A.; Ancona-Lezama, David; Mazloumi, Mehdi; Patel, Shail P.; McLaughlin, Jonathan W.; Ferenczy, Sandor R.; Mashayekhi, Arman; Shields, Carol L.
Abstract : Purpose: The aim of this study was to evaluate retinal microvascular abnormalities following plaque radiotherapy of choroidal melanoma (CM) using wide-field swept-source optical coherence tomography angiography (OCTA). Design: Single-centre retrospective review. Methods: Retrospective case series of 105 CM patients treated with I-125 plaque radiotherapy and imaged with wide-field (15 × 9 mm) SS-OCTA from March 2018 to August 2018 at the Ocular Oncology Service, Wills Eye Hospital (Philadelphia, PA). Results: At mean follow-up of 49 months (range 4–297) after plaque radiotherapy, there were 52 eyes (50%) with clinically evident radiation retinopathy (CERR) and 53 eyes (50%) without CERR. Comparison (CERR vs controls) revealed foveal avascular zone enlargement (1.7 vs 0.23 mm 2, P  = 0.03) and reduction of capillary vascular density (CVD) in the superficial and deep plexus in the total wide-field (43% vs 47%, P  < 0.001, and 46% vs 48%, P  = 0.001, respectively), peripapillary region (66% vs 77%, P  < 0.001, and 66% vs 72%, P  = 0.001, respectively), and papillomacular bundle (60% vs 68%, P  < 0.001, and 61% vs 64%, P   =  0.03, respectively). Comparison (no CERR vs controls) revealed nonsignificant foveal avascular zone enlargement (1.20 vs 0.23 mm 2, P  = 0.16) and reduction of CVD in the superficial plexus (46% vs 47%, P  = 0.008), and not the deep plexus (48% vs 48%, P  = 0.42) of the total wide-field. Comparison of irradiated eyes (CERR vs no CERR) showed reduction of CVD in the superficial and deep plexus of the total wide-field (43% vs 46%, P  < 0.006, and 46% vs 48% P  < 0.02, respectively), peripapillary region (66% vs 74%, P  < 0.001, and 66% vs 72% P  < 0.01, respectively), and superficial plexus in the papillomacular bundle (60% vs 65%, P   =  0.03). Conclusions: Following plaque radiotherapy for choroidal melanoma, wide-field swept-source optical coherence tomography angiography demonstrates retinal microvascular abnormalities in the CVD in eyes with and without CERR. These findings are important in early detection and monitoring of radiation retinopathy.